Smartphone apps in rare disease care: a Dutch perspective on effective implementation - Willemse, Ilse H. J.; Mol, Marit; van Diggelen, Rozanne J. A.; van den Haak, Pieter; van de Warrenburg, Bart P. C. (Frontiers in Digital Health, 2025)
Smartphone-based health applications offer promising opportunities for personalized and continuous monitoring in healthcare. However, many apps remain confined to research settings and are never implemented in clinical practice. Moreover, the development and implementation of apps for rare diseases is significantly lagging behind. This perspective outlines six key themes critical to the successful development and implementation of health apps, drawing on insights from Dutch stakeholders. These include: stakeholder collaboration, development, ownership, financing, integration into hospital-based care, and patient use. Our perspective additionally discusses specific barriers, including regulatory constraints, funding challenges, and usability limitations, alongside facilitators such as co-creation with end users, early stakeholder involvement, implementation planning, and leveraging existing care networks. Specific challenges for rare diseases, such as limited patient populations, funding constraints, and difficulties in clinical validation and regulatory compliance, are also addressed, with potential solutions proposed. This perspective offers concrete recommendations to support the transition of health apps from research to clinical practice. Sustainable implementation requires early and ongoing stakeholder engagement, flexible strategies adapted to small-scale contexts, a strong focus on end users’ needs, and an impact-driven implementation plan already established at the start of development.